Alpha-amylase inhibitory activity of collagen hydrolysate from Asian bullfrog skin and its application in dark chocolate - Sylvia Indriani; Soottawat Benjakul; Azis Boing Sitanggang; Supatra Karnjanapratum; Sitthipong Nalinanon (Cogent Food & Agriculture, 2024)
The present study aimed to investigate the in-vitro antidiabetic activity of collagen hydrolysate (CH) from Asian bullfrog skin and its application as a bioactive compound in dark chocolate bars. Papain (3% [w/w]) was used to obtain CH with a simultaneous conjunction of ultrasound. CH possessed α-amylase inhibitory activity with an IC50 value of 3.60 mg/mL, while results from inhibition reaction kinetics revealed that CH inhibited α-amylase in a non-competitive mode. Different concentrations (0.5, 1.0, and 2.0% [w/w]) of CH were then fortified into dark chocolate bars, and the physicochemical characteristics, breaking strength, and rheological behaviour of the resulting chocolate were investigated and compared with a control (without CH addition). A higher level of CH significantly enhanced antidiabetic activity against α-amylase (p ≤ 0.05) in chocolate bar. Chocolate bar with 2% CH complied with the nutritional claim requirement for ‘source of protein’ with lower fat content and energy value, while sensory evaluation revealed good organoleptic properties.
Keywords: Protein Hydrolysis and Bioactive Peptides; Enzyme Production and Characterization; Food Chemistry and Fat Analysis